2014
DOI: 10.1186/s12884-014-0403-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between maternal blood pressures and offspring size at birth in Southeast Asian women

Abstract: BackgroundMaternal blood pressures in pregnancy is an important determinant of offspring size at birth. However, the relationship between maternal blood pressures and offspring’s size at birth is not consistent and may vary between ethnic groups. We examined the relationship between maternal peripheral and central blood pressures and offspring size at birth in an Asian multi-ethnic cohort, and effect modifications by maternal ethnicity and obesity.MethodsWe used data from 713 participants in the Growing Up in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
2
4
0
4
Order By: Relevance
“…Apart from that, both the mean of birth length and also head circumference were the lowest in severe preeclampsia (47.62±4.16 cm and 31.62±2.34 cm respectively). The result was similar to the study by Lim et al 23 which declared that peripheral systolic blood pressure would decrease birth weight, birth length, head circumference, and placental weight (all p<0.05). Each 1 SD (11.1 mmHg) increase of peripheral systolic blood was inversely associated with birth weight (-35.56 g; 95% CI=-66.57 to -4.54), birth length (-0.16 cm; 95% CI=-0.32-0.01), head circumference (-0.09 cm; 95% CI=-0.19-0.02), and placental weight (-8.78 g; 95% CI=-18.74-1.19).…”
Section: Discussionsupporting
confidence: 80%
“…Apart from that, both the mean of birth length and also head circumference were the lowest in severe preeclampsia (47.62±4.16 cm and 31.62±2.34 cm respectively). The result was similar to the study by Lim et al 23 which declared that peripheral systolic blood pressure would decrease birth weight, birth length, head circumference, and placental weight (all p<0.05). Each 1 SD (11.1 mmHg) increase of peripheral systolic blood was inversely associated with birth weight (-35.56 g; 95% CI=-66.57 to -4.54), birth length (-0.16 cm; 95% CI=-0.32-0.01), head circumference (-0.09 cm; 95% CI=-0.19-0.02), and placental weight (-8.78 g; 95% CI=-18.74-1.19).…”
Section: Discussionsupporting
confidence: 80%
“…Our data is in accord with previous studies that have reported an increased prevalence of small-for-gestational-age offspring in women with PCOS ( 5 , 29 ) with no difference in gestational age at delivery. It is recognized that mothers with higher blood pressure had offspring with lower birth weight ( 30 , 31 ) that we also showed here; however, in addition we report the novel finding of a negative correlation between maternal blood pressure in the second trimester and baby birth weight at delivery that may suggest a functional relationship between baby birth weight and maternal blood pressure as early as the second trimester. When considering potential indicative metabolic biomarkers of birth weight, our data revealed that SBP at delivery was the strongest predictor of low birth weight.…”
Section: Discussionsupporting
confidence: 71%
“…Higher PP was associated with lower birthweight in a cohort of 50 normotensive women from the Netherlands (99). Also, European (100) and Asian studies (101) have shown that elevated SBP and DBP were associated with impaired fetal growth. Although few studies have addressed hypotension as a potential risk factor for SGA, we found that low PP (but not low SBP, DBP, or MAP) was associated with SGA fetuses in our cohort of women participating in normal pregnancy follow up.…”
Section: Bp Measurements and Symphysis-fundal Heightmentioning
confidence: 86%